Memes, social videos, infográficos, citações : conteúdos visuais das redes sociais como proposta curricular para as artes visuais no ensino secundário - Aristimuño, Felipe (2018)
This article discusses the possibility of incorporating visual content from social networks, such as memes, social videos, infographics, and quotes, in the curricular development of visual arts in secondary education. In order to achieve this, a theoretical-practical methodology is proposed, arising from the selection of the curriculum components of History of Culture and Arts, present in Humanistic Scientific Visual Arts courses of secondary school level in Portugal. Consequently, we proposed a teacher-training workshop in creating social media contents for students of the master’s degree in art education of the Faculty of Fine Arts of the University of Lisbon